THE EFFECT OF BANKING ZAKAT AND CORPORATE SOCIAL RESPONSIBILITY ON THE PROFITABILITY RATIO OF SHARIA COMMERCIAL BANKS IN INDONESIA - Windari Windari; Abdul Nasser Hasibuan (IAIN Batusangkar, 2021)
This research is supported by not fit the theory to fact. Based on data obtained from syariahcommercial banks in indonesia as much as the percentage of the charity bank 9, banking corporate socialresponsibility and return on assets in fluctuation, but the increase that happened to the charity banking andcorporate social responsibility is not always followed by increase return on assets. The study aimed to identifythe charity banking and corporate social responsibility to the ratio of profitability syariah commercial banksin indonesia 2013-2018 good on this fact and simultaneously. This research is quantitative research, the dataderived from secondary data with the data format + cross-section 2013-2018 years time series. Data analysistechniques in a regression panel estimate data, with the t and the f. as using software analyzed eviews 9. Theresult showed on this fact charity banks significant impact on return on assets syariah commercial banksin indonesia, corporate social responsibility on this fact no significant impact on return on assets syariahcommercial banks in indonesia. Simultaneous meanwhile zakat banking and corporate social responsibilityhaving significant influence to return on assets syariah commercial bank in indonesia the R2 of 0.633020 or63.30 percent and 36.70 percent affected by other variables that not discussed in this study.